(untitled) (Journal of the College of Basic Education, 2022)
An optical system was designed to focus Nd-Yag laser beams with a wavelength of 1.06 micrometers and high energy within (1KJ) and the diameter of the laser beam (50) mm in a focus with a diameter of about (6) micrometers. The small number of lenses used and their lightness were taken into account to reduce the loss in laser energy passing through the optical system. The PSF, the LSF, the amount of energy accumulated in the focus, the spot size, and the amount of aberration were used as parameters to evaluate the designed system. The results showed the quality of the design. The results also showed that to focus a laser beam with a diameter greater than 55 mm, this requires the use of aspherical lenses instead of spherical lenses.